Biopolymer Film Embedded ZnO Nanoparticles for Antimicrobial Application and Fresh Fruit Preservation - Quynh, Mai Thuy; Anh, Mai Kieu; Khai, Dao Quang; Tru, Nguyen Van; Duong, Nguyen Hoang; Yen, Dang Thi; Huong, Nguyen Thi Thu; Thuy, Luong Thi Minh; Doanh, Sai Cong; Thanh, Pham Van; Thien, Nguyen Duy; Quynh, Luu Manh; et al. (VNU Journal of Science: Natural Sciences and Technology, 2024)
In this study, we reported on the synthesis of carboxymethyl cellulose biopolymer film containing ZnO nanoparticles (CMC – ZnO), oriented for antibacterial , and fruit preservation applications. The SEM and TEM image results show that the ZnO nanoparticles (ZnO NPs) on the CMC biopolymer film have a spherical structure that is irregularly agglomerated with each other. The CMC - ZnO biopolymer film has been proven to effectively inhibit the growth of E. coli . At the same time, it is considered a promising application in packaging and preserving fruits and foods. As a proof of concept, we used this CMC biopolymer film containing zinc oxide for avocado preservation. The results show that its freshness could be maintained for up to 35 days.